2005
DOI: 10.1080/j.0001-6349.2005.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin levels and phagocytes in the cervical mucus plug at term of pregnancy

Merete Hein,
Astrid C. Petersen,
Rikke Bek Helmig
et al.

Abstract: Acta Obstet Gynecol Scand 2005; 84: 734-742. # Acta Obstet Gynecol Scand 84 2005Background. To characterize the potential for adaptive immune protection in cervical mucus plugs with respect to immunoglobulin isotypes and effector cells (phagocytes).Methods. Thirty-one cervical mucus plugs were collected from healthy women in labor at term. The cervical mucus plugs were allocated either to analysis of immunoglobulins by enzyme-linked immunosorbent assay (ELISA), gel chromatography and Western blotting (n ¼ 20) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
(83 reference statements)
0
13
0
1
Order By: Relevance
“…Patients with a CL 15 mm had a higher rate of positive AF culture [26% (15/57)] than patients with a CL !15 mm [3.8% (13/344)] [220]. It is unclear if a short cervix leads to compromised innate immunity following the loss of the anti-microbial properties of the cervical mucus plug [224][225][226][227][228][229] and predisposes to ascending intra-amniotic infection, or alternatively, if intra-amniotic infection leads to a short cervix.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a CL 15 mm had a higher rate of positive AF culture [26% (15/57)] than patients with a CL !15 mm [3.8% (13/344)] [220]. It is unclear if a short cervix leads to compromised innate immunity following the loss of the anti-microbial properties of the cervical mucus plug [224][225][226][227][228][229] and predisposes to ascending intra-amniotic infection, or alternatively, if intra-amniotic infection leads to a short cervix.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a number of actions that could contribute to prevention of PTB. These actions may be seen at the following four different levels: (i) reducing cervical stromal degradation (16), altering the barrier to ascending infection (17), inhibiting cervical ripening and improving cervical length in patients with a short cervix (18); (ii) decreasing the concentration of myometrial oxytocin receptors (19), reducing contraction frequency (13) and possibly acting as a tocolytic agent (20); (iii) attenuating the response to hemorrhage and inflammation in the decidua (21); and (iv) suppressing prostaglandin synthesis in fetal membranes and in the placenta, reducing apoptosis (21) and altering estrogen synthesis (22). Additionally, progesterone alters endocrine‐mediated effects in the fetus (22).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have demonstrated a reduction in the rate of preterm birth with intravaginal progesterone administration to women with premature cervical shortening3, 4. Progesterone is known to affect several cellular physiologies in each tissue of the reproductive tract including the cervix5–21.…”
Section: Introductionmentioning
confidence: 99%